Distribution of marine birnavirus in cultured marine fish species from Kagawa Prefecture, Japan - T Isshiki; T Nagano; K Kanehira; S Suzuki (Journal of Fish Diseases, 2004)
To determine the distribution of marine birnavirus (MABV) in cultured populations of different marine fish species, 1291 pooled tissue samples from 2672 fish belonging to 22 species and one hybrid were collected from Kagawa Prefecture, Japan, during 1999–2001. Using cell‐culture MABV was isolated from three species: yellowtail, Seriola quinqueradiata Temminck & Schlegel (positive number/sample number, 10/419), amberjack, S. dumerili (Risso) (4/72), and Japanese flounder, Paralichthys olivaceus (Temminck & Schlegel) (41/481). Using PCR on MABV‐negative samples, the MABV genome was detected in the same three species [yellowtail (9/409), amberjack (4/68) and Japanese flounder (93/440)] and two additional species, spotted halibut, Verasper variegatus (Temminck & Schlegel) (5/11), and goldstriped amberjack, S. lalandi Valenciennes (1/5). These MABV‐positive species can be taxonomically divided into two groups: the genus Seriola and flatfish. In Japanese flounder, MABV was detected during all seasons, and the infection rate was correlated with water temperature. Aquaculture sites with MABV‐positive fish were evenly distributed over the surveyed area, suggesting that MABV is widely distributed at aquaculture sites in Kagawa Prefecture. The nucleotide sequence at the variable region, the VP2/NS junction, revealed that the 39th base mutation occurs host‐specifically for flatfish. Flatfish are suspected to be the main reservoir of MABV and might be responsible for establishing the infection cycle in aquaculture environments.